Emergency Response Mechanism and Improvement of Hazardous ChemicalsAccidents in Qing Yang City. Issue 5 (May 2020) - Gai, Ke; Chen, Wanchun; Zhong, Shan
Abstract: This paper analyzes the distribution of hazardous chemicals production enterprises and the construction of rescue teams. In order to further strengthen and perfect the emergency mechanism of hazardous chemicals in our city, the problems in the safety management of hazardous chemicals production enterprises in our city are analyzed, and related requirements are put forward, so as to reduce the occurrence of hazardous chemicals accidents and reduce the degree of hazards. It is also recommended that enterprises and governments establish a sound accident emergency response system, and use emergency plans, emergency resources, emergency command, and emergency response to build a safe emergency response platform for hazardous chemicals. In order to improve the accident emergency mechanism.